Turn Taking Analysis on Loki Series Season 1 (Episode 2) - Aura Akmalia Yudanti; Tyoma Risca Cahyanti Purba (Universitas Musamus Merauke, 2023)
The purpose of this study is to do Discourse Analysis by identifying different kinds of turn-taking on Loki series season 1, episode 2. The focus of this study is to analyze Turn-taking pauses, backchannels, and overlaps on conversations among characters in Loki series season 1, episode 2, which is 53:12 minutes long. Various conversational aspects emerge when characters interact, prompting analysis of pauses, overlaps, and backchannels. Using a qualitative approach, data was gathered by watching the episode. After collecting the data, it was classified into categories of pauses, overlaps, and backchannels, followed by reasons for each classification. The findings revealed one hundred and twenty six pauses, eleven instances of backchannels, and five overlapping conversations. This categorization helps in understanding the dynamics of conversational interactions in the series, providing insights into how pauses, overlaps, and backchannels function in dialogue. The study contributes to the broader field of conversational analysis, highlighting the intricate details of character interactions in televised media, and giving contribution to the educational field.